A new gamma density measurement method for cased-hole formation evaluation. (June 2022) - Zhang, Qiong; Li, Yulian; Jin, Ya; Niu, Decheng; Meng, Yuexin; Wang, Yang; Li, Lvlin; Ge, Yi; Wu, Huilin; Liu, Feng; Shang, Jie
Abstract: Under complex well conditions, cased-hole formation evaluation has become increasingly important since it effectively reduces downhole operational risks compared to open hole. However, thru-casing gamma density measurement proves much more challenging than open-hole measurement due to gamma's weak penetration power, and difficulties in obtaining accurate cement evaluation. To overcome these challenges, a new gamma density measurement method is introduced in this work. The method composes three aspects: 1) Construction of an extensive Monte Carlo modelling database based on an existing 4-detector gamma density tool; 2) Correlation identification between detectors and environmental parameters by designing a fast forward detector response model; 3) Development of an inverse formation model whose solution targets at both formation density and cement density in circumstances when cement is uncertain. In this process, a novel cement invasion model is also proposed and employed to obtain constraints to accelerate the computation. The correctness of the method is firstly verified using modelled data, then is applied to an offshore well with open-hole density log as the reference. Results show accurate density could be obtained where cement condition is uncertain. Highlights: Formation density behind wellbore casing is accurately measured. A new constraint model minimizes the uncertainty of field cement density. An offshore test validates the correctness of obtained cased-hole density.